Opening research sites in multicentre clinical trials within the UK: a detailed analysis of delays. Issue 9 (16th September 2014) - Kearney, Anna; McKay, Andrew; Hickey, Helen; Balabanova, Silviya; Marson, Anthony G; Gamble, Carrol; Williamson, Paula
Abstract : Objective: To investigate the length of time taken to open UK research sites in multicentre clinical trials and to identify reasons for any delays. Design: A case study, recording key milestone dates from the time a site receives ethical approval through to opening to recruitment. Delay reasons were prospectively logged by trial staff at a minimum of fortnightly periods using a coding system. Setting: SANADII, a phase IV pragmatic trial, managed by the Clinical Trials Research Centre, Liverpool. The trial seeks to work with over 100 National Health Service (NHS) sites to meet its recruitment target of 1510 patients. Outcomes and analysis: The primary outcome was time from Multicentre Regional Ethics Committee (MREC) approval to site opening using survival analysis. Where sites took over a specified time to reach milestones (>3 months from MREC to Site Specific Information (SSI) submission, >30 days from SSI validation to local R&D approval, or >30 days from local Research and Development (R&D) approval to opening to recruitment), the longest continuous delay during that milestone was identified. Results: The median opening time for participating sites was 9.7 months (IQR 6.2 to Not Reached). SSI submission took 7 months (IQR 4.1–12.3) from ethics approval, R&D approval took 16 days (IQR 5.0–32.0) from SSI validation and site opening took 15 days (IQR 8.5–40.0) following R&D approval. The longest delays before SSI submission resulted from negotiating excess treatment costs, finalising logistics, collecting CVs and ongoing participation discussions. Conclusions: While recently imposed targets are reducing the time taken for R&D departments to approve valid applications, the time taken to open UK research sites remains excessive and must be reduced. At present significant public funds are being used inefficiently in order to navigate NHS systems, challenging the resolve of trial teams and the competitiveness of the UK.